Character: Jacobo Arroyave (2010)
Jacobo is 11 years old. His friends say he is shy, intelligent, a good friend. He likes technology and wants to be an engineer to create products that are good for the environment. He loves to play soccer, read a lot, and play drums. Read more about him in this interview.